2011
DOI: 10.1055/s-0031-1296488
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Asthma Therapy by a Novel Formoterol Multidose Dry Powder Inhaler

Abstract: The objective of this post-marketing surveillance (PMS) was the evaluation of efficacy, tolerability, and acceptance of the advanced formoterol (CAS 73573-87-2) multidose dry powder inhaler (MDPI) Formatris 6 microg/12 microg Novolizer (FN) in asthmatic patients (n = 5219) in a real-life setting. A total of 2727 patients (52%) received concomitant anti-inflammatory treatment exclusively via a budesonide Novolizer (BN). Efficacy of the FN was assessed by measurement of peak expiratory flow (PEF) and forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, for the overall group no significant difference for preference was seen between the inhalers. In an earlier 4-week observational study, Novolizer was rated as better than previously used inhalers by 83% of patients [28]. In a further 4-week observational study, an improvement in compliance due to the control mechanisms of the Novopulmon Novolizer was observed in 80% of the 3057 patients [29].…”
Section: Previous Inhaler Usementioning
confidence: 88%
“…However, for the overall group no significant difference for preference was seen between the inhalers. In an earlier 4-week observational study, Novolizer was rated as better than previously used inhalers by 83% of patients [28]. In a further 4-week observational study, an improvement in compliance due to the control mechanisms of the Novopulmon Novolizer was observed in 80% of the 3057 patients [29].…”
Section: Previous Inhaler Usementioning
confidence: 88%
“…Studies that utilised a Likert scale or symptom diary were primarily used to monitor how the severity or frequency of cough changed in response to a treatment therapy. A number of studies reported reduction in cough frequency and severity scores with bronchodilator therapy [66][67][68][69]. Inhaled corticosteroid therapy was also reported to be effective either alone [70] or in combination with bronchodilators [71][72][73].…”
Section: Non-validated Patient-reported Outcome Measures For Coughmentioning
confidence: 99%